6 - The History of Makerere Institute of Social Research (MISR) and her Place in the Study of the Social Sciences in Africa - Stanley Baluku Bakahinga Mbalibulha (Journal of Higher Education in Africa, 2022)
Following the research steps of the Rhodes-Livingstone Institute which started in 1937, three new research institutes were formed in the British Empire viz. The East African Institute of Social Research (later re-named Makerere Institute of Social Research [MISR]); The West African Institute of Social Research (WAISER) and the West Indies Institute of Social Research (WIISR). This expansion in knowledge production had its own logic and history as well as links to the deepening studies in social sciences, especially anthropology. Over the years, the Institute at Makerere has continued with a fledgling relationship with Makerere University with which it shares a history since 1948. We attempt to place the institute within a history; a history of social science knowledge production; a history of an endogenous institute attempting to attain indigeneity and space.